Differential Interspecific Adaptation to Abiotic Stress by Plantago Species - António Teixeira; António Teixeira; Peter E. Toorop; Pietro P. M. Iannetta (Frontiers in Plant Science, 2020)
The success of seed-based conservation and restoration efforts using native plant species is largely determined by ensuring two key life history transitions are accommodated. These are from “seed to germinated seed” and “germinated seed to established seedling.” In turn, optimization of these life history transitions is determined by a “genetic × environmental” interaction and later largely characterized by localized climatic (abiotic) conditions. It is these environmental stress factors that can act as natural selection agents for specific plant–trait combinations, or phenotypes. In turn, such adaptation may also limit a species range. To test the relationship between these two early plant life history stage transitions, “seed to germinated seed” and “germinated seed to established seedling,” the attributes were characterized for two species of Plantago that occupy contrasting environments and since these species have potential for native seed-based habit restoration and conservation. The species were Plantago coronopus (L.), localized at lower and drier altitudes, and Plantago lanceolata (L.), characterized as occupying higher and wetter altitudinal clines. Seeds were collected from 20 accessions of six natural populations spanning four European countries for both P. lanceolata and P. coronopus. Seed germination (G) and seedling establishment (S) data were determined at six temperatures (T) and six water potentials (Ψ), and the data obtained were analyzed using a generalized linear model (GLM). The results indicate that P. coronopus has adapted physiologically to its high-altitude conditions such that seed germination and seedling establishment may be more readily achieved in this cooler environment where water is less limiting. In contrast, the lower θT of P. lanceolata better facilitates more efficient seed germination and seedling establishment in drier and warmer clines of lower altitude. In addition to establishing a genotypic (species) underpin for seed and seedling trait differences observed, the insights gained may also be exploited to best deploy each species in situ for seed-based conservation and restoration efforts.